Overcoming digital transformation barriers: Chinese SMMEs in the sharing economy - Xiaosheng, Ji; Hua, Zhang; Jin, Zhang; AL-Bukhaiti, Khalil; Wan, Anping (Frontiers in Manufacturing Technology, 2025)
Digital transformation is critical for small and medium-sized manufacturing enterprises (SMMEs) in China to enhance competitiveness within the sharing economy, particularly in the production capacity domain, which accounts for 32.75% of the sharing economy market. However, SMMEs face significant technological, financial, organizational, and cultural barriers that hinder their digitalization efforts. This study conducts a comprehensive literature review to analyze barriers to digital transformation and the role of sharing economy platforms. It proposes strategies leveraging chain-centric, industry-brain, and shared service cloud platforms. A case study of Company F, an SMME in the elevator industry, is analyzed using quantitative financial data (2015–2022) and qualitative interviews, employing statistical methods (e.g., regression analysis) and thematic analysis with NVivo to evaluate the impact of a shared service platform provided by Company L. The case study reveals that Company F's digital transformation, facilitated by Company L's shared service platform, significantly improved profitability and operational efficiency. Post-transformation (2019–2022), the mean main business profit margin increased from 32.65% to 45.94%, and total asset turnover rose from 0.64 to 0.84. Regression analysis confirmed significant gains (p < 0.05 for profit margin, p < 0.01 for asset turnover). Qualitative findings highlight enhanced maintenance efficiency, streamlined spare parts management, and increased collaboration, despite a temporary decline in 2020 due to the COVID-19 pandemic. The sharing economy, through data-sharing and collaborative platforms, mitigates SMMEs' resource constraints and fosters digital transformation. These findings underscore the potential of shared platforms to overcome transformation barriers, offering actionable strategies for SMMEs and policymakers. While focused on China, the study suggests broader applicability to other middle-income countries, emphasizing the need for supportive digital ecosystems and regional considerations to ensure equitable transformation.